Pengaruh Jumlah Angkatan Kerja dan Tingkat Kemiskinan Terhadap Indeks Pembangunan Gender (IPG) Dalam Ekonomi Islam (Analisa Data Panel Periode 2015-2025) - Zadli Rahma Ilahi; Fatih Fuadi; Is Susanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study aims to analyze the influence of the workforce and poverty levels on the Gender Development Index (GDI) in 10 provinces on Sumatra Island for the period 2015–2025 from an Islamic economic perspective. The main issue raised is the low increase in the GDI despite a decrease in the poverty rate and an increase in the workforce during that period, thus raising questions about the effectiveness of both variables in promoting gender equality. This study uses a quantitative approach with panel data regression analysis. The data used are secondary data sourced from the Central Bureau of Statistics with a total of 110 observations (balanced panel). Model selection is carried out through the Chow, Hausman, and Lagrange Multiplier tests which indicate that the Random Effect Model (REM) is the best model. To overcome violations of the autocorrelation assumption, this study applies Robust Standard Errors with White Period. The results show that simultaneously, the workforce and poverty levels have a significant effect on the GDI (Prob. F = 0.0098). Partially, the poverty level has a negative and significant effect on the GDI at the α = 5% level, while the workforce has a positive but insignificant effect at the α = 5% level. The R-squared value of 8.28% indicates that many other factors influence the GDI. This study contributes to filling this gap by integrating panel data analysis on Sumatra Island with an Islamic economic perspective, specifically the maqasid sharia (Islamic principles), which emphasize the principles of social justice (al-'adl) and public welfare (maslahah). The results are expected to inform policy recommendations for gender-equitable poverty alleviation in Sumatra.